The Tate Gallery 1982-84 : Illustrated Biennial Report. - Tate Gallery, London (London : Tate Gallery, 1984)
Constant, Tinguely, Jean ; Rainer, Arnulf ; Beuys, Joseph ; Kiefer, Anselm ; Baselitz, Georg ; Kounellis, Jannis ; Blake, Peter ; Cox, Stephen ; Longo, Robert ; etc.
Contents: Historic British Collection Acquisitions, Modern Collection Acquisitions, Print Collection ; Exhibitions ; Education ; Publications ; ...
Engels
boek